FENOMENA KOMUNIKASI FEMALE DISC JOCKEY DI KOTA PEKANBARU - Atika Hersa Febriasistari; Welly Wirman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Female Disc Jockey becomes a phenomenon that thriving nowadays. Female Disc Jockey comes from different circle such student and even housewife. Until now the phenomenon of Female Disc Jockey is getting more develop marked by increasing the number of their performance on many event such night club in Pekanbaru. On their performance they often wearing sexy clothes. Meanwhile their work place is close to some kind of negative such alcohol, drugs, freesex and led to a negative stigma from many people. This research aims to find out motives, meaning, and communication experiences of Female Disc jockey In Pekanbaru.This study uses qualitative research with phenomenological approach. The subject of this research is consist of five Female Disc Jockeys in Pekanbaru who has been chosen using the snowball technique. This study used data collection techniques observation, depth interviews, and documentation. To achieve the validity of the data, researcher used the extension of participation, triangulation, and adequacy of reference.The results showed first, the motive of Female Disc Jockey in Pekanbaru consists of Because motive that is hobby, trend, intercourse milieu, and fad. While in order to motive which is popularity, recognized by citizen, and parent support. The second, meanings given by Female Disc Jockey is as an experience, fun job, and way of life. The third, communication experience categorized into two, pleasant communication experience in form of support and acceptance of family, sense of comfort toward work environment of Disc Jockey, and support and aceptance from the surrounding environment. And unpleasant communication experience form are prevention or risistance from family, harassment and sense of uncomfort toward activities on work environment of Disc Jockey, and insults, bad perspective, and also unfriendly aceptance from the surrounding environment such intercourse milieu, social networking sites and neighborhood.Key Words: Communication Phenomenon, Female Disc Jockey, Phenomenology, Symbolic Interaction